Short dual antiplatelet therapy duration in high bleeding risk patients undergoing PCI for non-ST-elevation acute coronary syndrome. (3rd October 2022) - Cao, D; Valgimigli, M; Sartori, S; Spirito, A; Snyder, C; Mehran, R
Abstract: Background: Patients undergoing percutaneous coronary intervention (PCI) for acute coronary syndrome (ACS) remain at increased risk of recurrent ischemic events. An abbreviated dual antiplatelet therapy (DAPT) duration as short as 1 month has been suggested for those at high bleeding risk (HBR). Whether the benefits of 1-month DAPT are preserved in HBR patients presenting with non-ST-elevation ACS (NSTE-ACS) is subject of debate. Purpose: To assess the impact of NSTE-ACS presentation on the ischemic and bleeding outcomes of HBR patients undergoing PCI with a cobalt-chromium everolimus-eluting stent followed by a 1-month versus 3-month DAPT. Methods: The XIENCE Short DAPT Program encompasses three prospective, international, single-arm studies evaluating the safety and efficacy of a 1-month (XIENCE 28 USA and Global) or 3-month (XIENCE 90) DAPT duration. The program enrolled HBR patients who had undergone successful XIENCE stent implantation for acute or chronic coronary syndrome (excluding ST-elevation ACS). Event-free subjects discontinued DAPT at 1 or 3 months post-PCI. The primary endpoint was the composite of all-cause death or myocardial infarction (MI), while the key secondary endpoint was Bleeding Academic Research Consortium (BARC) type 2–5 bleeding between 1 and 12 months post-PCI. Ischemic and bleeding events associated with 1-month versus 3-month DAPT were assessed according to clinical presentation using propensity-score (PS) adjustment. Results: Out of 3, 364 HBR patients (n=1, 392 on 1-month DAPT and n=1, 972 on 3-month DAPT), 1164 (34.6%) underwent PCI for NSTE-ACS. At 12 months, the risk of death or MI was similar between 1- and 3-month DAPT in patients with (adjHR 1.12, 95% CI 0.73–1.70) and without NSTE-ACS (adjHR 0.92, 95% CI 0.65–1.29; p-interaction = 0.33). Landmark analysis between 1 and 3 months post-PCI showed significant treatment effect modification according to clinical presentation (p-interaction = 0.03) with greater benefit of 1-month DAPT in stable patients. BARC 2–5 bleeding was consistently reduced in both NSTE-ACS (adjHR 0.58, 95% CI 0.38–0.90) and stable patients (adjHR 0.86, 95% CI 0.63–1.18; p-interaction = 0.15). Conclusions: Among HBR patients undergoing PCI with an everolimus-eluting stent, 1-month compared with 3-month DAPT was associated with similar 1-year risk of ischemic events and reduced bleeding, irrespective of clinical presentation. Between 1 and 3 months post-PCI, however, stable patients seemed to derive greater net benefit from 1-month DAPT compared to those with NSTE-ACS. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Abbott